Socio-economic determinants and mortality patterns among children with spina bifida at Ruharo Mission Hospital, Western Uganda: A retrospective cross-sectional study. - Ndyowaawe, Arron Bram; Matovu, Daniel; Kazibwe, Francis (Student's Journal of Health Research Africa, 2025)
Background Spina Bifida (SB) is a significant cause of childhood morbidity and mortality in low-resource settings like Uganda. While clinical management is crucial, the role of socioeconomic determinants on survival outcomes remains underexplored. This study investigates the association between socioeconomic factors and mortality patterns among children with SB in Western Uganda. Methods A retrospective study design with a mixed-methods approach was conducted, a review of 152 medical records of children with SB (2013–2023) with qualitative focus group discussions involving 20 caregivers and 15 health workers. Quantitative data were analyzed using descriptive statistics, Firth logistic regression, and Kaplan-Meier survival analysis. Qualitative data were analysed thematically. Results The study revealed a high mortality rate of 65.1% (99/152). Multivariate analysis identified key socioeconomic determinants significantly associated with increased mortality: caregiver unemployment (β=1.53, OR=4.62, p=0.045), use of unprotected water sources (β=2.18, OR=8.83, p<0.001), and living 5-10 km from the health facility (β=4.42, OR=83.7, p=0.007). Most deaths (49.5%) occurred in infancy (1-11 months). Survival analysis showed a median survival time of 3-4 years, with infections being the leading cause of early death. Qualitative findings from caregivers and health workers highlighted family financial constraints, stigma, transportation barriers, and health system gaps (e.g., shortages of supplies and specialists) as critical challenges. Conclusion Mortality among children with Spina Bifida in Western Uganda is high and is profoundly influenced by modifiable socioeconomic determinants. Caregiver unemployment, poor water and sanitation, and geographical barriers to healthcare are significant predictors of mortality among children with SB. Recommendations Effective interventions must extend beyond clinical care to include socioeconomic support, inclusive livelihood interventions, such as financial protection schemes, income-generating activities, improved WASH infrastructure, decentralization of services, and community sensitization to reduce stigma. A multi-sectoral approach is essential to improve survival and quality of life for this vulnerable population of children with SB.